Harnessing technology in education: The function of RIPPLES model in ICT utilization in public secondary schools of Amhara, Ethiopia - Shimelis Gebeyehu Kebede; Melaku Mengistu Gebremeskel; Sifelig Taye Nigatu (PLoS ONE, 2025)
This study examined factors influencing the utility of ICT in enhancing teaching and learning effectiveness in secondary schools in the state of Amhara, Ethiopia. It specifically explored the effects of financial resources, infrastructure, personnel, policy, learning, evaluation, and support, as well as teachers’ and students’ perceptions of ICT utility. A correlational research design was employed, involving 739 teachers and 758 students selected through multistage sampling. Data were collected using a questionnaire and then analyzed using confirmatory factor analysis, independent-samples t-tests, and multiple regression analyses. Findings showed that the specified antecedents explained 65.9% and 52.5% of the variance in ICT utility for teachers and students, respectively. Support and access to ICT infrastructure significantly predicted ICT use, while ICT policy was the least influential factor. The t-test indicated a small difference between teachers’ and students’ perceptions (t = 2.771, d = 0.143), with both groups reporting below-average confidence in ICT’s usefulness. The study concludes that while ICT has the potential to enhance teaching and learning in secondary schools, its effective utilization is hindered by inadequate infrastructure, limited support, and weak policy implementation. To maximize ICT’s educational impact, policymakers and school leaders must adopt practical, evidence-based strategies that bridge the gap between policy intentions and classroom realities. They should strengthen technical and administrative support, provide adequate infrastructure, and offer ongoing training. Policymakers and educational leaders must also review ICT policies to ensure alignment with practical implementation needs.